Eduard J. Gramberg, Fondo y forma del humorismo de Leopoldo Alas, "Clarín". Instituto de Estudios Asturianos, Oviedo, 1958; 265 pp. - Muñiz-Huberman, Angelina (El Colegio de México, 1964)
Se reseñó el libro: Fondo y forma del humorismo de Leopoldo Alas, "Clarín".